2021
DOI: 10.14202/vetworld.2021.2244-2250
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory, behavioral, and nutritional response of tryptophan application on poultry

Abstract: Tryptophan is an essential amino acid for all animals that was discovered through casein hydrolysis. The use of tryptophan as feed additives has been attracting the attention of many nutritionists because it cannot be synthesized enough in an animal's body. Tryptophan or precursor to the vitamin niacin in the diet is important, and its supplementation for poultry is determined to improve the amino acid balance and promote the poultry's growth performance through enhancing appetite, feed efficiency, and protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…As Phe is metabolized to Tyr to produce the precursor of the catecholamine neurotransmitters, such as dopamine, which activity in the brain is closely related to SFP behavior ( Kops et al, 2017 ). Additionally, tryptophan metabolism affects the homeostasis of the animal's gut-brain axis, enhancing the body's immune response or the immunomodulatory activity through the kynurenine pathway ( Fouad et al, 2021 ), and affecting the behavioral responses (e.g., pecking behavior, stress-related, fearfulness) via the 5-HT metabolic pathway ( Linh et al, 2021 ). Here, we found that differential metabolites between the 2 FP phenotypes were mainly enriched in the tryptophan metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…As Phe is metabolized to Tyr to produce the precursor of the catecholamine neurotransmitters, such as dopamine, which activity in the brain is closely related to SFP behavior ( Kops et al, 2017 ). Additionally, tryptophan metabolism affects the homeostasis of the animal's gut-brain axis, enhancing the body's immune response or the immunomodulatory activity through the kynurenine pathway ( Fouad et al, 2021 ), and affecting the behavioral responses (e.g., pecking behavior, stress-related, fearfulness) via the 5-HT metabolic pathway ( Linh et al, 2021 ). Here, we found that differential metabolites between the 2 FP phenotypes were mainly enriched in the tryptophan metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its anti-inflammatory, anti-oxidant and anti-apoptotic activities in a variety of cells and tissues, nicotinate is actively involved in the prevention of many pathological processes 31 , 32 . Nicotinate is mainly synthesized in the liver through the kynurenine pathway, which is the major catabolic route of tryptophan 33 , 34 . From E14 onwards, nicotinate was not detected in the allantoic fluid, while kynurenine accumulated, and to a greater extent, in the pHu− line compared to the pHu+ line.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, peripheral serotonin increased intestinal motility and reduced plasma leptin and adiponectin concentrations, which can decrease appetite [ 159 ]. In poultry, insufficient tryptophan has been known to decrease serotonin synthesis [ 162 ]. However, most studies have focused on stress mitigation and meat quality, but not feed intake.…”
Section: Hormones From Enteroendocrine Cells On Feed Intake Controlmentioning
confidence: 99%